Coaches` emotional intelligence and athletes` psychological need satisfaction in taekwondo: Coaching behaviour as a mediator - Kim, S.; Hwang, S.; Kim, B. (Archives of Budo, 2020)
Background and Study Aim: Coaches` role in sports is crucial. Their emotional intelligence and behaviour affect athletes` motivational processes. This study cognitive aim is knowledge about the interrelations among emotional intelligence, coaching behaviour and psychological need satisfaction.